2010
DOI: 10.18779/cyt.v3i1.43
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico Serológico (Rosa De Bengala) Y Molecular (Pcr) De Brucelosis en Humano

Abstract: ResumenE l objetivo de esta investigación fue: Determinar y comparar la presencia de Brucelosis del personal que labora en los camales de los cantones, Buena Fé, Quevedo, El Empalme y Pichincha, utilizando la prueba serológica Rosa de Bengala (RB) y la técnica molecular (PCR). Se utilizó como fuente de ADN y anticuerpos sangre periférica. De un total de 115 muestras de sangre recolectadas al personal que labora en los camales como faenadores y operadores, 54 (47%) y 15 (13%) fueron positivas con RB y PCR respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Cevallos and coworkers (2010) also performed a conventional PCR technique, obtaining a sensitivity value of 75% and one of 92% for specificity, in comparison with the RBPT technique [11]. On developing the PCR technique utilizing whole blood, it was observed that the technique is fast, that its manipulation is facilitated, and that it diminishes the risk of infection; in addition, it allowed for simultaneous identification of the genus and the species due to the use of the multiple-PCR variant, and it provides overwhelming epidemiological reports due to that it identifies the most prevalent species in a determined population.…”
Section: Discussionmentioning
confidence: 99%
“…Cevallos and coworkers (2010) also performed a conventional PCR technique, obtaining a sensitivity value of 75% and one of 92% for specificity, in comparison with the RBPT technique [11]. On developing the PCR technique utilizing whole blood, it was observed that the technique is fast, that its manipulation is facilitated, and that it diminishes the risk of infection; in addition, it allowed for simultaneous identification of the genus and the species due to the use of the multiple-PCR variant, and it provides overwhelming epidemiological reports due to that it identifies the most prevalent species in a determined population.…”
Section: Discussionmentioning
confidence: 99%